Information Access and Resource Sharing with Persistent Identifiers (LIS TODAY, 2024)
Persistent identifiers (PIDs) are essential for information access and resource  discovery in scientific journal management systems. It provides a unique and  permanent reference identification number for digital objects, enabling researchers  to locate access quickly and cite the data. The names of various persistent identifiers  (PIDs) are Archival Resource Key (ARK), Digital Object Identifier (DOI), Handle  System, and Persistent Uniform Resource Locator (PURL). This article deals with  PIDs’ characteristics and power, enabling data sharing, collaboration, and advancing  research. The paper also discusses PIDs’ benefits, applications, and future direction.  Uses of persistent identifiers transform the impact of the research landscape.
Keywords: Archival Resource Key; Persistent Identifiers; Persistent Uniform Resource Locator; Digital Object Identifier; Data Repositories; Interoperability